2018
DOI: 10.1016/j.fuel.2018.05.054
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the reduction kinetics of high loaded CuO-based materials suitable for the Ca/Cu looping process

Abstract:  The reduction reaction kinetics of highly loaded CuO-based materials using H 2 , CO and CH 4 have been determined in a TGA both in powder and pellet form  A shrinking core model (SCM) with kinetic control has been successfully applied to describe the evolution of the reduction conversion of particles and pellets  The possibility of using different reducing gases in the reduction/calcination stage has been analyzed using the kinetic parameters previously obtained  The energy released by one pellet during r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The material was pelletized and the final particle size was in a range 0.6-2 mm to form a homogeneous bed with the sorbent and catalyst. A detailed kinetic study has been also performed elsewhere to determine oxidation and reduction kinetics of the Cu-based material under suitable conditions for the process [41,42]. It was determined that the evolution of material conversion with time can be successfully predicted by a shrinking core model under chemical reaction control and cylindrical geometry.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The material was pelletized and the final particle size was in a range 0.6-2 mm to form a homogeneous bed with the sorbent and catalyst. A detailed kinetic study has been also performed elsewhere to determine oxidation and reduction kinetics of the Cu-based material under suitable conditions for the process [41,42]. It was determined that the evolution of material conversion with time can be successfully predicted by a shrinking core model under chemical reaction control and cylindrical geometry.…”
Section: Methodsmentioning
confidence: 99%
“…Momentum balance, Ergun equation [41,42] The wall-bed heat transfer coefficient (h w ) has been experimentally determined as described in the description of the rig. It has been determined as 9.5 W/m 2 K and allowed for an accurate fitting of the energy balance in the model.…”
Section: Reactor Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, operating temperature during calcination should be as low as possible with the aim of minimizing the amount of Cu needed in the Ca-Cu process. Typical values proposed for this reduction/calcination step fall down in the range of 850-870°C, which is enough for ensuring complete CaCO3 calcination and sufficiently fast CuO reduction kinetics under the conditions of this reduction/calcination stage (Díez-Martín et al, 2018;Fernández et al, 2016).…”
Section: Hydrogen Production Island Based On the Ca-cu Processmentioning
confidence: 99%
“…They found that a Cu/Ca molar ratio of 1.8 enabled both the CuO reduction and sorbent regeneration reaction fronts to advance jointly, reaching a maximum temperature in the bed of about 1143 K. Tan et al [19] synthesised a NiO/CuO composite and experimentally tested its catalytic activity for H2 production. Diez-Martin et al [20] experimentally investigated the reduction reaction kinetics with hydrogen, carbon monoxide and methane of two high-load CuO-based materials with different supports for Ca/Cu looping processes. They found that the reduction reaction was kinetically controlled for the Al2O3-supported material, while the internal diffusion resistance becomes predominant for the MgAl2O4-supported one.…”
Section: Sorption-enhanced Steam Methane Reforming (Se-smr) Representmentioning
confidence: 99%